The Students Ignorance In Practicing English Speaking - Nisa Aldira Lubis; Afrohul Fadhillah; Anisa May Azura; Susi Sahmarito Rambe; M. Arkan Syafiq; Didik Santoso (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Mastery of English has become an increasingly important requirement in this era of globalization. As an international language, English plays a crucial role in various aspects of life, ranging from education, career, to cross-cultural communication. In Indonesia, although English has been taught since elementary school level, there are still many students who experience difficulties in English speaking practice. This phenomenon raises concerns among educators and education stakeholders. Many university students have studied English for years but are still reluctant or unconfident to use it in everyday conversation. This reluctance is often referred to as